It's messy being authentic – lessons learned on the road to becoming an authentic leader. Issue 3 (8th June 2015) - Wright, Robin
Abstract : Purpose: – This is an exploration of authentic leadership of which there are as many forms as there are leaders. By stripping away professional and embracing a willing to be vulnerable and truthful, individuals can eventually find the core gift that they have to offer as a leader. Design/methodology/approach: – This is a personal story of one executive's journey to becoming an authentic leader – shaped by both quiet personal experiences and headline-shaping world events. Findings: – Embracing one's own vulnerability is an essential part in the journey to become an authentic leader. Authentic leaders see vulnerability not as a weakness, but as a necessary ingredient for innovation, creativity and change. The author sees the following as four important aspects of authentic leadership: the value of multiple perspectives, balance of EQ and IQ, development of internal honesty and external trust and the ability to commit to action. Research limitations/implications: – This is a personal journey with a sample size of one, so the conclusions are experiential and anecdotal in nature. Practical implications: – Companies and those in leadership positions need to examine ways that they can both formally and informally model and mentor both established and future leaders in discovering their own authentic leadership style. Originality/value: – For companies to be success with a modern workforce, old models of leadership need to be shed, and authentic leadership needs to become the norm. This means change for both established and rising leaders.